Can hepatitis C virus core antigen be used as a reliable marker of viral load for hepatitis C virus infection in genotype 4?. Issue 1 (January 2017) - Sayed, Moataz M.; El-Shafie, Ahmed I.; Fathy Hilal, Ahmed; Abdelsattar, Hoda A.
Abstract : Background: Anti-hepatitis C virus (HCV) antibody assessment and viral nuclear acid measurement are important in the HCV infection diagnosis and follow-up. Aim: The aim of this study was to analyze hepatitis C virus core antigen (HCV core Ag) positivity among anti-HCV antibody-positive patients with genotype 4 to determine the utility of testing of HCV core Ag for the diagnosis of HCV infection in comparison with HCV RNA levels. Patients and methods: Ninety patients with positive anti-HCV antibody test were included in this study. HCV PCR quantitative and HCV core Ag tests were measured in all patients. HCV core Ag was assessed using WKEA HCV-Ag assay. Results: HCV PCR was detectable in 78 patients. All patients were infected with genotype 4. Seventy-five patients with positive HCV PCR demonstrated HCV core Ag positivity. HCV core Ag was undetectable in all 12 patients with negative HCV RNA and was undetectable in three patients with positive HCV PCR. In this study, HCV core antigen sensitivity, specificity, positive predictive value, and negative predictive value were 96.15, 100, 100, and 80%, respectively, in relation to HCV RNA PCR results. There was a positive correlation between HCV RNA and HCV core Ag ( r =0.916, P <0.0001). Conclusion: The HCV core Ag is a rapid, cost-effective test with good correlation with the HCV PCR tests. It may have a role in HCV diagnosis and should be further evaluated for follow-up of the HCV infection.